Reconstructing Employment Access for Persons with Disabilities: MaqÄá¹£id asy-syarÄ«â€™ah-Based Dialectic of Regulation and Policy Implementation - Himawan Estu Bagijo; FX Sri Sadewo; Budi Raharjo; Nunuq Nuswardhani; Abd. Munib (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2026)
Although Law Number 8 of 2016 has been enacted as a guarantee of employment rights for persons with disabilities, there are indications of problems in the field. In East Java Province, persons with disabilities still experience limited access to formal employment. In fact, any progressive regulation, if not balanced with practice, will widen inequality. As a consequence, the cycle of poverty will continue among persons with disabilities. This study aims to analyze the dialectic between disability employment regulations and their implementation which is reconstructed with a policy approach from the perspective of uá¹£Å«l al-fiqh and maqÄá¹£id asy-syarÄ«â€™ah. This study combines quantitative and qualitative data, focusing on four districts in East Java Province. The findings in this study are two. First, the implementation of affirmative employment policies is still constrained by weak supervision, corporate resistance, and the dominance of economic considerations. Second, institutional mechanisms, especially the Disability Service Unit (ULD), have not functioned optimally due to limited capacity and a lack of cross-sector integration. Although normatively the policy has been in line with the principles of á¸¥ifáº“ an-nafs, á¸¥ifáº“ al-mÄl, and al-'adl, its implementation has not reached the optimal level of maá¹£laá¸¥ah. This research contributes by integrating institutional analysis and the perspective of maqÄá¹£id asy-syarÄ«â€™ah to encourage an inclusive and equitable employment system for persons with disabilities.